DESENVOLVIMENTO DE UM SISTEMA DE AQUECIMENTO E CONTROLE DE TEMPERATURA EM REATORES ANAERÓBIO - Nascimento, Karl B. X. D.; Almeida, Diego T. D.; Valdiero, Antonio C. (Salão do Conhecimento, 2013)
Resumo